Relationship among Iranian EFL Teachers’ Emotional Intelligence, Reflectivity and Burnout - Mohammad Hadi Mahmoodi; Rozhin Ghaslani (Iranian Journal of Applied Language Studies, 2014)
Few studies can be found which have directly addressed the issue of burn-out by considering the influence of teachers’ coping resources such as emotional intelligence and reflectivity especially in an EFL context. Therefore, in order to bridge this gap, the present study was conducted to investigate the relationship among teachers’ burnout, emotional intelligence, and reflectivity with a sample of 125 Iranian EFL teachers from several private language institutes in Kurdistan and Hamedan. Moreover, differences in the teachers’ burnout, emotional intelligence, and reflectivity scores were examined with respect to teachers’ teaching experiences. To answer the research questions, the Maslach Burnout Inventory-Educators Survey, Teacher Reflectivity Questionnaire, and Bar-On EQ-I Scale were used and Pearson Product-Moment Correlation, Multiple Regression and MANOVA analyses were utilized. The findings showed that emotional intelligence and reflectivity were reversely correlated with burnout, and they could both predict the level of burnout. The results of the study also revealed that there were significant differences between teachers’ level of emotional intelligence with respect to their teaching experience. However, no significant differences were found between teachers’ burnout and reflectivity with respect to their teaching experience. Implications of the study are discussed in details in the paper.